More favorite stories of Christmas past [compact disc, unabridged]. - Prebble, Simon; Bean, Joyce (Tantor Audio, 2008)
This anthology of Christmas stories will transport listeners back to the Christmases of their youth, when they first heard these classic holiday tales.